The brutalist [videorecording (Blu-Ray)] - Corbet, Brady, 1988-; Fastvold, Mona, 1981-; Brody, Adrien; Jones, Felicity; Pearce, Guy, 1967-; Alwyn, Joe, 1991-; Cassidy, Raffey; Martin, Stacy, 1990-; Laird, Emma; Bankolé, Isaach de; Nivola, Alessandro; Blumberg, Daniel, 1990-; et al. (A24 Films, 2025)
Escaping post-war Europe, a visionary architect arrives in America to rebuild his life. On his own in a strange new country, a wealthy industrialist recognizes his talent. But power and legacy come at a heavy cost.